1995
DOI: 10.1366/0003702953965687
|View full text |Cite
|
Sign up to set email alerts
|

Frequency/Wavelength Calibration of Multipurpose Multichannel Raman Spectrometers. Part II: Calibration Fit Considerations and Calibration Standards

Abstract: Approaches for frequency/wavelength calibration of multichannel Raman spectrometers are presented. These approaches are directed towards practical use in laboratories in which multipurpose or specialized applications result in the need for frequent spectrometer calibration. These approaches are also useful when the sample type or configuration does not permit calibration by more routine methods. Guidelines are presented for effective use of polynomials commonly found in spectrometer calibration software for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 7 publications
1
38
0
Order By: Relevance
“…To precisely assign a wave number to each individual detector channel, two types of external sources were used: calibration lamps and a reference compound whose Raman peak positions are known. Emission lines of low-pressure argon-mercury and mercury calibration lamps (Oriel Instruments, Stratford, CT), as well as indene, were used for calibration (6). Calibration points distributed over the whole spectral region of interest were fitted by a polynomial (WinSpec Software, Roper Scientific, Trenton, NJ).…”
Section: Raman Intravital Microscopementioning
confidence: 99%
“…To precisely assign a wave number to each individual detector channel, two types of external sources were used: calibration lamps and a reference compound whose Raman peak positions are known. Emission lines of low-pressure argon-mercury and mercury calibration lamps (Oriel Instruments, Stratford, CT), as well as indene, were used for calibration (6). Calibration points distributed over the whole spectral region of interest were fitted by a polynomial (WinSpec Software, Roper Scientific, Trenton, NJ).…”
Section: Raman Intravital Microscopementioning
confidence: 99%
“…In this way, wavelength uncertainties can be estimated at multiple locations within a spectrum. Wavelength calibration by Raman shift standards is usually achieved by applying polynomial fit functions that aim at establishing a relation between the column numbers of the CCD detector and the individual Raman lines [83]. In this context, Carter et al systematically compared first, second and third order polynomials for wavelength calibration of dispersive instruments.…”
Section: Wavelength Calibration In Dispersive Raman Spectroscopymentioning
confidence: 99%
“…The authors found furthermore, that the simplest calibration model, the linear model, gave reasonably good and robust calibration results. For example, linear models performed comparatively well in situations where erroneous band positions were purposely introduced into the calibration data [83]. Finally, linear models were found particularly valuable in case of extrapolation, i.e.…”
Section: Wavelength Calibration In Dispersive Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Barium sulphate has a strong band at 988 cm À1 , diamond a band at 1364 cm À1 and silicon a band at 520 cm À1 which are now used by some instrument manufacturers. In addition, indene [28], cyclohexane and sulphur have well-known band positions as measured on dispersive instruments. However calibrating relative peak heights is a rarely mentioned field.…”
Section: Calibrationmentioning
confidence: 99%